Cyclosporin A attenuating morphine tolerance through inhibiting NO/ERK signaling pathway in human glioblastoma cell line - Rashki, Asma; Mumtaz, Faiza; Jazayeri, Farahnaz; Shadboorestan, Amir; Esmaeili, Jamileh; Ejtemaei Mehr, Shahram; Ghahremani, Mohammad Hossein; Dehpour, Ahmad Reza (Technische Universität Dortmund, 2018)
Cyclosporin A (CsA) is known to have an immunosuppressive action. However, it is also attracting attention due to its effects on the nervous system, such as inhibiting the development and expression of morphine-induced tolerance and dependence through unknown mechanisms. It has been shown that CsA modulates the nitric oxide (NO) synthesis and extracellular signal-regulated kinases (ERK) activation, which are potentially involved in signaling pathways in morphine-induced tolerance in cellular models. Therefore, the current study was designed to evaluate the modulatory role of CsA on the MOR tolerance, by targeting the downstream signaling pathway of NO and ERK using an in vitro model. For this purpose, T98G cells were pretreated with CsA, calcineurin autoinhibitory peptide (CAIP), and NG-nitro-l-arginine methyl ester (L-NAME) 30 min before 18 h exposure to MOR. Then, we analyzed the intracellular cyclic adenosine monophosphate (cAMP) levels and also the expression of phosphorylated ERK and nitric oxide synthase (nNOS) proteins. Our results showed that CsA (1 nM, 10 nM, and 100 nM) and CAIP (50 μM) have significantly reduced cAMP and nitrite levels as compared to MOR-treated (2.5 μM) T98G cells. This clearly revealed the attenuation of MOR tolerance by CsA. The expression of nNOS and p-ERK proteins were down-regulated when the T98G cells were pretreated with CsA (1 nM, 10 nM, and 100 nM), CAIP (50 μM), and L-NAME (0.1 mM) as compared to MOR. In conclusion, the CsA pretreatment had a modulatory role in MOR-induced tolerance, which was possibly mediated through NO/ERK signaling pathway.
the involvement of calcineurin
EXCLI Journal;Vol. 17 2018
Keywords: Cyclosporin A; Morphine; Tolerance; Nitric oxide; T98G cells; Extracellular signal-regulated kinases; 610